The Use of Simalungun Language by Anak Boru Sanina in the Simalungun Wedding Ceremony (Sociolinguistic Studies) - Nurhasanah Purba (Lakhomi Journal Scientific Journal of Culture, 2020)
The purpose of this study was to determine the use of the Simalungun language in the traditional Simalungun wedding ceremony performed by Anak Boru Sanina. The research method used in this research is qualitative descriptive analysis. The results of this study indicate the existence of code mixing and code switching by Anak Boru Sanina using Simalungun, Indonesian and Javanese. This is because there is a mixture of cultures between the two brides. In this study the groom came from the Javanese tribe.